Practical reliability engineering - O'connor, Patrick D.T; Newton, David; Bromley, Richard (John Wiley & Sons, 2002)
Practical Reliability Engineering provides a comprehensive, up-to-date description of all the important methods for the design, development, manufacture and maintenance of reliable engineering products and systems. Students, engineers and managers alike will find this a valuable reference source. With emphasis firmly placed on the practical aspects of reliability engineering, the fourth edition provides extended coverage of mechanical, electronic and software failure mechanisms, design and testing. New sections include Petri nets for system reliability modelling, accelerated test and the M(t) data analysis method. Recent developments in international standardisation are discussed and guidance is provided on essential management issues. The inclusion of a draft Project Reliability Plan enhances the value to those involved in systems engineering and project management.